Effect of fund size on the performance of Australian superannuation funds. (5th March 2015) - Cummings, James R.
Abstract: This study examines the relationship between fund size and performance for two major superannuation industry sectors in Australia: retail and not‐for‐profit, using a unique but confidential database. Results suggest that members benefit from being invested in larger superannuation funds for three reasons: (i) larger not‐for‐profit funds provide diversification benefits of investing in more asset classes including unlisted property and private equity, (ii) larger funds in both sectors avoid the scale diseconomies in investment returns documented in studies of equity mutual funds and (iii) larger funds make substantial savings by spreading fixed operating costs (such as IT infrastructure) over a larger asset base.